Impact of mobile subscribers dual stack IPv4/IPv6 deployment - Pahlevi, Mohammad Dian; Soewito, Benfano (Communications in Science and Technology, 2018)
The use of CGNAT at PT. ZYX as a mobile telecommunication service provider cannot be relied as the solution to solve addressing needs against subscriber growth in future technology. Meanwhile, native IPv6 deployment is currently application-driven, which requires maturity support in either subscriber user equipment, network, and application itself. IPv4/IPv6 dual stack deployment was selected by PT. ZYX as stepping stone towards native IPv6 deployment. This paper analyzes the impact of dual stack IPv4/IPv6 deployment for mobile subscribers at PT. ZYX. After selecting the dual stack approach and completing the deployment, test and measurements were performed to confirm the connectivity also against the performance and node utilization to conclude the impact. The test confirmed successful connectivity and the measurements showed that the deployment gives significant enhancement of routing table size and NAT table in node utilization and does not cause performance drop of hop count, throughput, and download time.